EP101/#503 Relevance of genomic instability score, tumor mutational burden, and tumor infiltrating lymphocytes as biomarkers in uterine serous carcinoma. (4th December 2022) - Bloom, Elizabeth; Peters, Pamela; Whitaker, Regina; Previs, Rebecca; Strickland, Kyle; Timms, Kristen; Cummings, Shelly; Slavin, Thomas
Abstract : Objectives: Uterine serous carcinomas (USC) represent 10% of endometrial carcinomas but nearly 40% of deaths. We characterized genomic instability (GIS), tumor mutational burden (TMB), and density of tumor infiltrating lymphocytes (TILs) in patients with USC. Methods: A single institution, retrospective cohort study analyzed patients with USC following hysterectomy. In collaboration with Myriad Genetics, we determined GIS score and TMB from archived specimens. Cox proportional hazards models evaluated associations of molecular factors with survival. Using immunohistochemistry, we evaluated tumoral expression of CD3, CD4, CD8. T-tests were conducted to evaluate associations of TILs with GIS and tumor recurrence. Results: We evaluated 53 patients with USC; 66% (n=35/53) presented with advanced disease (stage III-IV). Median GIS was 31 (range: 0–52) and not associated progression-free survival (PFS) or overall survival (OS). Median TMB was 1.35; patients whose tumors exhibited TMB >1.35mutations/megabase (median) had improved PFS and OS (p=0.005, 0.002). Two tumors had elevated CD3+ TILs (>75th percentile) and low GIS (<=31). Tumors with elevated CD3+ and CD4+ immune cells had significantly higher mean GIS (p=0.013, p=0.002). Tumors with both low GIS and low-normal TILs (<=75th percentile) had lower recurrence rates (p=0.2). Conclusions: TMB >1.35 mutations/megabase was associated with improved survival. Alternate TMB thresholds may provide prognostic value for less immunogenic tumors, like USC. In this limited data set, GIS was not associated with survival or recurrence. Patients with low GIS and low-normal TIL infiltration had lower recurrence rates, unlike other solid tumors. Additionally, the presence of CD3/CD4+ immune cells may be a marker of GIS.